The Contribution of Bilingualism, Parental Education, and School Characteristics to Performance on the Clinical Evaluation of Language Fundamentals: Fourth Edition, Swedish - Andersson, Ketty; Hansson, Kristina; Rosqvist, Ida; Lyberg Åhlander, Viveka; Sahlén, Birgitta; Sandgren, Olof (Frontiers in Psychology, 2019)
Assessment of bilingual children in only one language fails to acknowledge their distributed linguistic competence and has been shown to overidentify language disorder in bilingual populations. However, other factors, sometimes associated with bilingualism, may also contribute to low results in language assessments. Our aim was to examine the impact of these factors on language abilities. We used the Clinical Evaluation of Language Fundamentals – Fourth Edition, Swedish (CELF-4) to investigate core language abilities of 224 7- to 8-year-old children. Results showed 30 and 80% of monolinguals and bilinguals, respectively, performing more than 1 SD below the normative sample mean, calling into question the clinical utility of the test. However, participant and school characteristics provided a deeper understanding of the skewed results. In isolation, bilingualism predicted 38% of the variance in the CELF-4 Core scores. With level of parental education entered the variance explained by the model increased to 52%, but the unique contribution of bilingualism was reduced to 20%. Finally, with information added on school characteristics and enrollment in the school’s recreation center the model explained an additional two percent, with the unique contribution of bilingualism further reduced to 9%. The results indicate an increased risk for low results on the CELF-4 Core when children present with multiple risk factors. This highlights the need to look beyond bilingualism in language assessment of bilingual children and adolescents and to consider other explanations to academic struggle. Available interventions must be considered and applied proportionately to their respective impact on the individual’s development.